A secondary battery

By optimizing the design of the negative electrode sheet, controlling the particle size distribution and coating surface density of the negative electrode active material, the lithium dendrites problem of lithium-ion batteries during fast charging is solved, and the rapid charging and long life of the battery is achieved, which improves the Battery safety and cycle performance.

CN115101803BActive Publication Date: 2024-12-17JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210824317.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2024-12-17
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to lithium dendrites to grow during fast charging, resulting in increased battery polarization, reduced power performance and safety risks, and it is difficult to take into account both fast charging and long life.

Method used

By controlling the relationship between the particle size distribution, coating surface density, specific surface area and battery capacity excess coefficient of the negative electrode active material in the secondary battery, a negative electrode sheet that satisfies 0.65≤U≤1.35 is designed to optimize lithium ion transmission. Path and battery structure to achieve a balance between fast charging and long life.

Benefits of technology

It realizes the efficient performance and long life of lithium-ion batteries during fast charging, reduces the growth risk of lithium dendrites, and improves the safety and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003745806430000081
    Figure BDA0003745806430000081
  • Figure BDA0003745806430000091
    Figure BDA0003745806430000091
  • Figure HDA0003745806440000011
    Figure HDA0003745806440000011
Patent Text Reader

Abstract

The present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, wherein the negative electrode membrane comprises a negative electrode active material, and the negative electrode active material satisfies 0.65≤U≤1.35; wherein U=β*C 负 *S 负 *D 50负 / CB,β=1.044cm ‑1 , C 负 is the surface density of the negative electrode membrane, in g / cm 2 ;D 50负 is the median particle size of the negative electrode active material, in μm; in g / cm 3 , S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g, CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area. The secondary battery provided by the present invention controls the relationship between the particle size distribution, coating surface density, specific surface area and battery capacity excess coefficient of the negative electrode active material in the secondary battery, so that the obtained battery has both long life and fast charging capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a secondary battery. Background Art

[0002] Rechargeable batteries have outstanding features such as light weight, high energy density, no pollution, no memory effect, and long service life, so they are widely used in mobile phones, computers, home appliances, power tools and other fields. Among them, charging time and service life are increasingly valued by end consumers and are also important factors limiting the popularization of rechargeable batteries.

[0003] In order to shorten the charging time, the battery must have the ability to charge quickly. If the battery itself does not have the ability to charge quickly, it will be easy for lithium dendrites to grow on the negative electrode surface, which will lead to a series of adverse effects on the battery, such as increased battery polarization, decreased battery power performance, and a sharp shortening of battery life. At the same time, during the use of the battery, the continuous growth of lithium dendrites may pierce the isolation membrane and cause an internal short circuit, which will bring safety hazards to the battery.

[0004] From a technical point of view, the key to determining the charging speed of a battery is the negative electrode. Therefore, providing a negative electrode and a secondary battery that can be quickly charged is a problem to be solved. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a secondary battery. The secondary battery provided by the present invention controls the relationship between the particle size distribution, coating surface density, specific surface area and battery capacity excess coefficient of the negative electrode active material in the secondary battery, so that the obtained battery has both long life and fast charging capability.

[0006] The present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, the negative electrode membrane comprises a negative electrode active material, and the negative electrode sheet satisfies 0.65≤U≤1.35;

[0007] Where U = β * C 负 *S 负 *D 50负 / CB,

[0008] β=1.044cm -1 ,

[0009] C 负 is the surface density of the negative electrode membrane, in g / cm 2 ;

[0010] D 50负 is the median particle size of the negative electrode active material, in μm;

[0011] S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g,

[0012] CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area.

[0013] Preferably, the negative electrode plate satisfies 0.75≤U≤1.10.

[0014] Preferably, it is characterized in that 1.08≤CB≤1.18.

[0015] Preferably, 5.0 μm ≤ D 50负 ≤18μm.

[0016] Preferably, 1.0m 2 / g≤S 负 ≤2.5m 2 / g.

[0017] Preferably, 0.85 g / cm 2 ≤C 负 ≤1.25g / cm 2 .

[0018] Preferably, the negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, and mesophase carbon microspheres.

[0019] Preferably, the graphite is selected from one or more of artificial graphite, natural graphite and modified graphite.

[0020] Preferably, at least a portion of the negative electrode active material is in the form of secondary particles.

[0021] Preferably, the negative electrode sheet is prepared according to the following method:

[0022] After mixing the negative electrode active material, conductive agent, thickener and binder, add deionized water as solvent and stir until the system becomes uniform to obtain negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector, dry it, and then cold press and cut it to obtain negative electrode sheets.

[0023] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder is 95.4:1.9:0.9:1.8.

[0024] Compared with the prior art, the present invention provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet includes a negative electrode membrane and a negative electrode current collector, and the negative electrode membrane includes a negative electrode active material, wherein the negative electrode active material satisfies 0.65≤U≤1.35; wherein U=β*C 负 *S 负*D 50负 / CB,β=1.044cm -1 , C 负 is the surface density of the negative electrode membrane, in g / cm 2 ;D 50负 is the median particle size of the negative electrode active material, in μm; in g / cm 3 , S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g, CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area. The secondary battery provided by the present invention controls the relationship between the particle size distribution, coating surface density, specific surface area and battery capacity excess coefficient of the negative electrode active material in the secondary battery, so that the obtained battery has both long life and fast charging capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the negative electrode active material used in Example 8;

[0026] Figure 2 This is a SEM image of the negative electrode active material used in Example 9. DETAILED DESCRIPTION

[0027] The present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, the negative electrode membrane comprises a negative electrode active material, and the negative electrode sheet satisfies 0.65≤U≤1.35;

[0028] Where U = β * C 负 *S 负 *D 50负 / CB,

[0029] β=1.044cm -1 ;

[0030] C 负 is the surface density of the negative electrode membrane, in g / cm 2 ;

[0031] D 50负 is the median particle size of the negative electrode active material, in μm;

[0032] S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g,

[0033] CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area.

[0034] In the present invention, the negative electrode plate satisfies 0.65≤U≤1.35. Within this range, the secondary battery has excellent fast charging capability.

[0035] Preferably, the negative electrode plate satisfies 0.75≤U≤1.10. Within this range, the secondary battery has a more excellent fast charging capability.

[0036] Where U = β * C 负 *S 负 *D 50负 / CB,

[0037] In the formula, β = 1.044 cm -1 ,

[0038] This relationship involves several key physical parameters that affect fast charging performance. In order to achieve fast charging performance of the battery, the negative electrode needs to meet the following conditions: First, the surface density C of the negative electrode film 负 As small as possible, which can reduce the congestion of lithium ion transmission between the positive and negative electrodes and reduce the average distance of lithium ion transmission between the positive and negative electrodes; second, the specific surface area S of the negative electrode active material 负 As large as possible, increasing the number of channels for lithium ions to embed in the negative electrode layer; third, the negative electrode particles are as small as possible, that is, the D50 representing the particle size is as small as possible, increasing the diffusion distance of lithium ions inside the negative electrode particles. However, the surface density of the negative electrode film, the specific surface area of ​​the particles of the negative electrode active material, the median particle size of the negative electrode active material, and the CB value, the value range of these parameters are also limited.

[0039] Among them, C 负 is the surface density of the negative electrode membrane, in g / cm 2 ; Use a one-ten-thousandth gram precision balance to measure the mass m1 of the electrode per unit area S' and the mass m2 of the current collector per unit area after single-sided coating, C 负 =(m1-m2) / S'. That is, C 负 The negative electrode membrane area is 1540.25mm 2 Coating weight, g / 1540.25mm 2 In the present invention, 0.85 g / cm 2 ≤C 负 ≤1.25g / cm 2 , C 负 Preferably, 0.85, 0.90, 0.95, 1.0, 1.05, 1.10, 1.15, 1.20, 1.25, or 0.85 to 1.25 g / cm 2 In the present invention, the surface density of the abdominal muscle membrane needs to be controlled within the range of 0.85 to 1.25 g / cm 2If the surface density is within the range, the energy density of the battery cell will be low if it is too low, and if it is too high, the thickness of the membrane will increase, resulting in increased impedance during the charge and discharge process, thereby reducing the fast charging capability. Controlling the surface density within the appropriate range can improve the fast charging capability and ensure that the battery energy density is not too low. The C value (surface density) can be mainly controlled by the coating machine to obtain a suitable surface density. For example, when using extrusion coating, the coating gap, slit gap, channel width, flow rate (pump speed), coating speed, etc. can be controlled to control the surface density.

[0040] D 50负 is the median particle size of the negative electrode active material, in μm; D 50负 It is the particle size corresponding to the cumulative volume percentage of the negative electrode active material reaching 50%. According to the national standard "GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method", the sample is dispersed under pressure and the particle size of the material is characterized by a laser particle size analyzer. The test results are expressed as the median particle size D 50 In the present invention, 5.0 μm ≤ D 50负 ≤18 μm, preferably 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, or any value between 5 and 18 μm. In the present invention, D of the negative electrode active material 50负 It needs to be controlled between 5 and 18 μm. If the particle size is too large, the chemical reaction speed is slow, and the particles are easy to break, resulting in increased internal resistance. If the particles of the negative electrode active material are smaller, the van der Waals force that needs to be overcome during embedding is also smaller, and the embedding is easier to carry out. Moreover, the smaller the particles, the more channels there are for lithium ion embedding and extraction, which is more conducive to quickly reaching a fully embedded lithium state. Under high-rate scanning conditions, the voltage hysteresis is smaller, that is, the high-current charge and discharge performance is better. However, if the particles of the negative electrode active material are too small, the larger the specific surface area that can contact the electrolyte, the more charge is consumed by the SEI film formed during the first charge and discharge process, and the greater the irreversible capacity loss.

[0041] S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g, according to the national standard "GB / T 19587-2004 Method for Determining the Specific Surface Area of ​​Solids by Gas Adsorption BET Principle", the test was carried out using an adsorption characterization analyzer. The powder sample to be tested was placed in a U-shaped sample tube, and a mixed gas containing a certain proportion of adsorbate was passed through the sample. The adsorption amount of the adsorbate molecule (N2) by the sample to be tested was determined based on the change in gas concentration before and after adsorption, thereby obtaining the specific surface area S 负 In the present invention, 1.0m 2 / g≤S 负 ≤2.5m 2 / g, preferably 1.0, 1.5, 2.0, 2.5, or 1.0 to 2.5m 2 In the present invention, when the specific surface area of ​​the graphite particles is controlled within a suitable range, lithium ion embedding can be made easier, which is conducive to quickly reaching a complete lithium embedding state, that is, the large current charge and discharge performance is better.

[0042] CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area. In the present invention, 1.08CB≤1.18, preferably 1.08, 1.10, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, or 1.08-1.18 g / cm 3 In the present invention, CB needs to be controlled at 1.08-1.18 g / cm 3 If the CB value is too large, the negative electrode consumes too much lithium, which will lead to too low initial efficiency, thus making the battery capacity too small. If the CB value is too small, it is easy to cause lithium precipitation. The metallic lithium on the surface of the negative electrode will react with the electrolyte, reducing the amount of active lithium and the amount of cyclable active lithium. The capacity decay becomes faster, so lithium precipitation will lead to a decrease in battery cycle performance. Therefore, only when the CB value is controlled within an appropriate range can the battery achieve a better fast charging effect.

[0043] At the same time, several key factors affecting fast charging performance involved in this relationship also have mutual constraints. When D50 is too large, it will indirectly affect S 负 Smaller, D50 is too big, while S 负 If it is too small, the impedance of the battery cell will increase and the charging capacity will decrease. In order to balance the impact on the charging capacity, the coating weight (surface density) will be reduced in the pole piece design. 负 , reducing the congestion of lithium ion transmission between the positive and negative electrodes, and reducing the average distance of lithium ion transmission between the positive and negative electrodes to improve the overcharge capacity. After the charging capacity is improved, under high-rate charging, the battery cell needs a higher CB value to ensure that the battery cell does not precipitate lithium, thereby ensuring better battery cycle performance.

[0044] The parameters in the relationship restrict each other. At the same time, the requirements for physical properties of fast charging performance and life cycle are different. In order to meet the fast charging and life requirements of the battery, the physical properties parameters and electrode design parameters are balanced. The value of the formula U composed of various parameters is within this range, which can ensure the cycle performance while meeting the fast charging requirements.

[0045] In the present invention, the negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, and lithium titanate. Among them, the graphite is preferably one or more of artificial graphite, natural graphite, and modified graphite.

[0046] In the present invention, at least a portion of the negative electrode active material is in the form of secondary particles. The particle structure of the negative electrode active material is often divided into primary particles and secondary particles. The primary particles have high compaction density, small specific surface area, good high temperature performance and long life; the secondary particles often have strong fast charging capabilities, because the secondary particles are granulated and sintered from small-diameter primary particles. Within the same compaction density and particle size range, the secondary particles have a larger specific surface area, and the diffusion distance of lithium ions inside the particles is shorter, which is more conducive to fast charging.

[0047] During the sintering process of the secondary particles, some materials with binder functions such as asphalt are needed to stick them together in advance, and then sinter them at high temperature and graphitize them. Among them, the commonly used characterization method for particle structure is SEM, which can have a very clear resolution for secondary particles.

[0048] In the present invention, the screening process of the secondary battery parameters is specifically as follows: the present invention first screens the negative electrode active material, and then controls the negative electrode membrane parameters, as well as the parameters of the positive electrode sheet and the negative electrode sheet.

[0049] Among them, the smaller the particle size of the negative electrode active material, the better the fast charging performance, but the cycle performance becomes worse. If the surface density is too low, the energy density of the battery cell will become low. If the surface density is too high, the thickness of the membrane will increase, resulting in increased impedance during charging and discharging, thereby reducing the fast charging capability. Controlling the surface density within an appropriate range can improve the fast charging capability and ensure that the battery energy density is not too low. In the design of the negative electrode sheet of the present invention, the surface density C of the negative electrode membrane is increased. 负 , median particle size D of negative electrode active material 50 , the specific surface area S of the negative electrode active material 负 , CB value, taking all into consideration, when the negative electrode membrane satisfies 0.65≤U≤1.35, the fast charging and cycle performance of the battery can be taken into account, and a secondary battery with fast charging capability and long cycle life can be obtained.

[0050] The surface density of the negative electrode membrane is C 负 The median particle size D50 of the negative electrode active material and the specific surface area S of the negative electrode active material can be adjusted by controlling the cold pressing parameters of the electrode. 负 , can be adjusted by selecting the appropriate negative electrode material. The CB value can be adjusted by the coating ratio of the active material of the positive and negative electrodes.

[0051] The present invention has no special limitation on the preparation method of the secondary battery, and the preparation method is well known to those skilled in the art.

[0052] In the present invention, the negative electrode sheet is preferably prepared according to the following method:

[0053] After mixing the negative electrode active material, the conductive agent, the thickener and the binder, adding the solvent deionized water, stirring until the system is uniform, to obtain the negative electrode slurry;

[0054] In the present invention, the negative electrode active material, the conductive agent, the thickener, and the binder are mixed in a mass ratio of 95-97:1-2:0.6-1:1-2.5, and a preferred ratio is 95.4:1.9:0.9:1.8.

[0055] The negative electrode slurry is evenly coated on the negative electrode current collector, dried, and then cold pressed to adjust the surface density and cut to obtain the negative electrode sheet. The obtained negative electrode sheet meets the above condition of 0.65≤U≤1.35.

[0056] Wherein, the negative electrode active material is selected from the negative electrode active materials described above.

[0057] The present invention has no particular limitation on the specific types of the conductive agent, thickener and binder, and any types known to those skilled in the art may be used.

[0058] In the present invention, the conductive agent is preferably acetylene black;

[0059] The thickener is preferably CMC;

[0060] The binder is preferably SBR.

[0061] In the present invention, the positive electrode sheet is preferably prepared according to the following method:

[0062] After mixing the positive electrode active material, conductive agent and binder, add the solvent and stir until the system is uniform to obtain positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, dried, and then cold pressed and cut to obtain positive electrode sheets.

[0063] The present invention has no particular limitation on the specific types of the positive electrode active material, the conductive agent and the binder, and any type known to those skilled in the art may be used.

[0064] The positive electrode active material is preferably lithium iron phosphate;

[0065] The conductive agent is preferably acetylene black;

[0066] The binder is preferably PVDF.

[0067] The present invention has no particular limitation on the specific types of the electrolyte and the separator, and any specific types known to those skilled in the art may be used.

[0068] The secondary battery provided by the present invention controls the relationship between the particle size distribution, coating surface density, specific surface area and battery capacity excess coefficient of the negative electrode active material in the secondary battery, so that the obtained battery has both long life and fast charging capability.

[0069] In order to further understand the present invention, the secondary battery provided by the present invention is described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0070] Examples and Comparative Examples

[0071] To prepare the positive electrode sheet, the positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, the solvent NMP is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain the positive electrode sheet.

[0072] To prepare the negative electrode sheet, the negative electrode active material, conductive agent acetylene black, thickener CMC, and binder SBR are mixed in a mass ratio of 95.4:1.9:0.9:1.8, and deionized water is added as a solvent. The mixture is stirred in a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet. Figures 1-2 , Figure 1 This is a SEM image of the negative electrode active material used in Example 8; Figure 2 This is a SEM image of the negative electrode active material used in Example 9.

[0073] To prepare an electrolyte, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0074] A separating film is prepared and a polyethylene film is selected as the separating film.

[0075] To prepare a lithium-ion battery, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0076] Dynamic performance test: At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example was fully charged at xC (1≤x≤6) and fully discharged at 1C for 50 times, and then the lithium-ion battery was fully charged at xC (1≤x≤6), and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, x was tested from large to small, and the charging rate when the area of ​​lithium deposition on the negative electrode surface was less than 5% was the fast charging capability.

[0077] Cyclic performance test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged at 1C, discharged to the cut-off voltage, and the discharge capacity was recorded as C1. After standing for 30 minutes, they were charged and discharged at 1C again, and the discharge capacity was recorded as C2. This operation cycle was repeated until C n / C1 is less than 0.8, and n is recorded. The larger n is, the better the cycle performance is. n greater than 2500 cycles indicates excellent cycle performance, n in the range of 2000-2500 cycles indicates average cycle performance, and n less than 2000 cycles indicates poor cycle performance.

[0078] See Table 1 for the results.

[0079] Table 1

[0080]

[0081]

[0082] It can be seen from Table 1 that in Examples 1-11, the D50, specific surface area and CB value of the materials all meet the requirements of 0.65≤U≤1.35, and all have excellent fast charging capabilities, among which 0.75≤U≤1.10 will have even better fast charging capabilities. In Comparative Example 1, the graphite particle size is not within the range, and although the U value is within the range, the cycle performance is poor. In Comparative Examples 2-4, U is greater than 1.35, and the fast charging performance is poor. Compared with Example 3, Comparative Example 5 has the same material, the corresponding CB value is reduced, and the fast charging capability is reduced. The CB value of Comparative Example 6 is less than 1.08, lithium plating occurs, and the cycle performance of the battery deteriorates.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, the negative electrode membrane comprises a negative electrode active material, and the negative electrode sheet satisfies 0.7≤U≤0.76; Where U = β * C 负 *S 负 *D 50负 / CB, β=1.044cm -1 , C 负 is the surface density of the negative electrode membrane, in g / cm 2 ; D 50负 D is the median particle size of the negative electrode active material, in μm, 6.35 μm ≤ 50负 ≤7.01μm; S 负 is the specific surface area of ​​the negative electrode active material, in m 2 / g, 1.77m 2 / g≤S 负 ≤2.196 m 2 / g, CB is the ratio of the capacitance of the positive electrode sheet to the capacitance of the negative electrode sheet with the same area, 1.145≤CB≤1.

18.

2. The secondary battery according to claim 1, characterized in that: The negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, and mesophase carbon microspheres.

3. The secondary battery according to claim 2, characterized in that: The graphite is selected from one or more of artificial graphite, natural graphite and modified graphite.

4. The secondary battery according to claim 1, characterized in that: At least a portion of the negative electrode active material is in the form of secondary particles.

5. The secondary battery according to claim 1, characterized in that: The negative electrode sheet is prepared according to the following method: After mixing the negative electrode active material, conductive agent, thickener and binder, add deionized water as solvent and stir until the system becomes uniform to obtain negative electrode slurry; evenly coat the negative electrode slurry on the negative electrode collector, dry it, and then cold press and cut it to obtain negative electrode sheets.

6. The secondary battery according to claim 5, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder is 95-97:1-2:0.6-1:1-2.5.